Applying Multi-Criateria Analysis to Select the Location for Poultry Farm: A Case Study in Somalia - MOHAMED, MOHAMED ABDULKADIR (İstanbul Kültür Üniversitesi, 2025)
This research addresses the challenges of poultry farm site selection in Mogadishu, Somalia, by filling a gap where multi-criteria decision-making (MCDM) approaches have been rarely applied. The study aims to enhance sustainable operational success by analyzing six key criteria: land cost, accessibility of transportation, proximity to the market, safety, utilities, and biosecurity. Applying Analytic Hierarchy Process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), four alternative sites (A1) Markazka, (A2) Daaru Salaam, (A3) Hilwaa, (A4) Jaziira, were carefully analyzed based on expert opinions. The findings indicate that Hilwaa is the most suitable option for SAFA Company due to its infrastructure, access to market, biosecurity, and safety. Despite its limited infrastructure, Jaziira ranked second, driven by its strong biosecurity and low land cost. Markazka shows potential if infrastructure improvements are made, while Daaru Salaam was considered the least attractive due to biosecurity and high land cost. This study not only demonstrates the practical value of MCDM methods in poultry site selection but also sets the way for future studies to expand and refine criteria used in similar studies. Keywords: poultry farm, site selection, AHP, TOPSIS, MCDM, Mogadishu, decision-making.
Keywords: Poultry Farm; Site Selection; AHP; TOPSIS; MCDM; Mogadishu; DecisionMaking